Equivalence classes of matrices over a finite field - Gary L. Mullen (International Journal of Mathematics and Mathematical Sciences)
Let Fq=GF(q) denote the finite field of order q and F(m,q) the ring of m×m matrices over Fq. Let Ω be a group of permutations of Fq. If A,BϵF(m,q) then A is equivalent to B relative to Ω if there exists ϕϵΩ such that ϕ(A)=B where ϕ(A) is computed by substitution. Formulas are given for the number of equivalence classes of a given order and for the total number of classes induced by a cyclic group of permutations.